The Relationship Between Diabetes Knowledge and Diabetes Self-Care Behaviors in Relation to Diabetes Distress in Type 2 Diabetes Mellitus: A Cross-Sectional Study in Eastern Taiwan - Chen YC; Huang YH; Lee CH (Diabetes, Metabolic Syndrome and Obesity)
Yi-Chien Chen,1,2 Yi-Hua Huang,1 Chao-Hsien Lee2 1Department of Nursing, Taipei Veterans General Hospital, Yuli Branch, Hualien, Taiwan, Republic of China; 2Department of Social Work, Meiho University, Pingtung, Taiwan, Republic of ChinaCorrespondence: Chao-Hsien Lee, Department of Social Work, Meiho University, No. 23, Pingguang Road, Neipu, Pingtung County, 91202, Taiwan, Republic of China, Tel +886-8-7799821 ext. 6400, Fax +886-8-7784416, Email x00002167@meiho.edu.twIntroduction: Diabetes is a highly prevalent metabolic disease worldwide. In Taiwan, healthcare services emphasize self-management strategies and interventions focusing on self-care. However, there is a lack of literature on diabetes distress (DD). Therefore, this study aims to explore the relationship between demographic characteristics, diabetes knowledge, and diabetes self-care behaviors with diabetes distress among Type 2 diabetes mellitus (T2DM) patients and identify predictive factors.Methods: This study employs a cross-sectional survey, targeting T2DM patients from the internal medicine outpatient clinic of a regional hospital in eastern Taiwan. Participants were recruited through purposive sampling from April 11, 2023, to May 16, 2023. The study examines the correlation between diabetes knowledge, diabetes self-care behaviors, and diabetes distress, as well as other influencing factors. The data analysis methods include (1) differences in diabetes knowledge, diabetes self-care behaviors, and diabetes distress scores, analyzed using t-tests or ANOVA, (2) Scheffe’s tests for significant differences identified by ANOVA to locate group differences in means, and (3) multiple regression analysis to identify key predictive factors of diabetes distress.Results: The findings reveal that both diabetes knowledge (β=− 0.046, p=0.029) and diabetes self-care behaviors (β=− 0.186, p=0.006) significantly predict diabetes distress. Additionally, gender (β=0.251, p=0.004), family history of diabetes (β=0.213, p=0.017), and diabetes complications (β=0.228, p=0.018) are significant predictors of diabetes distress. The overall F-test reached significance (F=7.61, p< 0.001), and the explanatory power of the regression model (R²=0.17) is statistically significant, indicating that diabetes knowledge, diabetes self-care behaviors, gender, family history of diabetes, and diabetes complications are important predictors of diabetes distress in T2DM patients. These findings can provide valuable insights for clinicians in identifying risk factors for diabetes distress and understanding the factors that influence diabetes distress in T2DM patients.Conclusion: It is crucial to integrate the assessment and management of diabetes distress into routine diabetes care and even implement distress screening during the health promotion stage. Strengthening the ability of healthcare professionals to identify diabetes distress through early detection of risk factors and providing individualized interventions and care plans tailored to T2DM patients is of great importance.Keywords: type 2 diabetes, diabetes knowledge, diabetes self-care behaviors, diabetes distress, diabetes knowledge questionnaire, DKQ-18, diabetes self-care behaviors scale, problem areas in diabetes scale, PAID